The experiences of parental divorce on the psychological well- being among high school students in China - Jiarui, Ma; Che Amat, Muhammad Asyraf; Salam, Syahrul Nizam (Macrothink Institute, Inc., 2023)
High school students in China who have experienced parental divorce may face significant psychological and life challenges. The purpose of this study is to explore and understand the impact of parental divorce on the psychological well-being among Chinese high school students. This qualitative study adopted a descriptive phenomenological approach. A total of eight participants were selected through a purposive sampling technique in Qinghai Province, China. The data was gathered using a semi-structured interview to gain in-depth understanding and to obtain sufficient information from the participants. The research data were collected to answer two research questions: 1) what are the experiences of high school students from parental divorced families? 2) how does parental divorce affect high school students’ psychological well-being? The following themes were identified in high school students who experience parental divorced in their families: 1) difficulties adapting with new family environment, 2) becoming overly independent, and 3) rising economic problems after the divorce. Four themes were also identified on how parental divorce experiences affect students’ psychological well-being: 1) low life satisfaction and happiness, 2) emotional instability, 3) sense of insecurity, and 4) arising of mental health risks and problems. The study will prepare organizations that provide mental health services and school counsellors to a better understanding of the thoughts, feelings, and behaviours of high school students who are affected by parental divorce and provide them with necessary supports.